Memories of my melancholy whores - Garcia Marquez, Gabriel, 1928-; Grossman, Edith; Penguin Books (London : Penguin Books, 2007)
On the eve of his ninetieth birthday, a unnamed journalist and lifelong bachelor decides to give himself a gift of one night of wild sex with a virgin.
Keywords: Fiction, Spanish -- Translation into English; Journalist -- Fiction; Prostitutes -- Fiction